Inventorying the Dynamics of Shoreline Changes of the Maheshkhali Island, Cox’s Bazar, Bangladesh - Khan, Ebadullah; Ali, Mohammad (The Jahangirnagar Review, 2024)
This study mainly focused on the exploration of spatial and temporal dynamics of the shoreline change of the Maheshkhaki Island. Besides this, what is the scenario of erosion and accretional processes along the shorelines that has been illustrated. Shoreline is generally defined as the confluence place of landmass and waterbodies is considered to be one of the most dynamic processes in the coastal zone. Maheshkhali is an offshore Island of the Bay of Bengal and it is a unique island due to its geophysical locations. The Eastern and North-eastern part of the island is separated from mainland by a narrow channel and western part of the Island is open to the see. So, Strong wave actions as well as wind movement is prevalent in the western part. Remote sensing tools and techniques are the significant platform for processing the satellite imageries for identifying the shoreline changes. Landsat Multi-spectral Scanner (MSS) imageries have used for 1972, near infrared band (NIR, Band-4) is effective for shoreline detection. Landsat TM imagery of 1996 and Landsat OLI imagery of 2020 have been used for image data, near infrared (NIR, band 5) is effective for shoreline detection. 20 cross-sections have been taken and the width distance of each cross section has been measured for analysing the shoreline shifting direction and pattern. The total erosion and accretion from 1972 to 2020 are 1633.28 hectares and 2254.62 hectares respectively. The percentage of variation between erosion and accretion is (+) 38.04%, which indicates overall the accretion level is higher than the erosion level. The substantial shoreline shifting has been occurred in cross-section (XS)-9 due to erosion and accretion where the amount of shifting is (-) 4.38 kms from the sea to land and (+) 3.21 kms from interior land to the sea respectively. Overall, for all cross-sections, most of the shifting tendency has been observed in the western part of the Island.